GCC Countries : From Oil Dependence to Diversification - Iqbal, Zubair; Fasano-Filho, Ugo. (Washington, D.C. : International Monetary Fund, 2003)
This paper presents an overview of the unprecedented economic and social transformation witnessed by the member countries of the Cooperation Council of the Arab States of the Gulf (GCC)-Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates-over the last three decades.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet